The Sufficiency-Based Circular Economy—An Analysis of 150 Companies - Bocken, Nancy M. P.; Niessen, Laura; Short, Samuel W. (Frontiers in Sustainability, 2022)
The circular economy has become a popular paradigm in the business and policy spheres. It can support sustainable development by aiming to safeguard the resources to mitigate negative impacts on the climate and the environment and to sustain our current and future generations. Yet, despite progress with circular economy initiatives, there is a risk of focusing on incremental innovations with little real impact, and possibly even creating serious negative rebound effects. This study suggests that the concept of “sufficiency” is inadequately represented in the current circular economy discourse and innovations, and this may be undermining real progress. In this paper, the Sufficiency-based Circular Economy paradigm is introduced. We investigate the following questions: What is the role of business in the sufficiency-based circular economy? What are the institutional limitations to the role of business as a driver for the transition and how might these be overcome? We conduct a “practice research” by analyzing company cases of sufficiency practices in a business context. We analyse 150 business cases to identify how their organizational strategies support sufficiency and what type of innovations they exemplify within this transition. We investigate seven core business elements for economic transformation (purpose, ownership, governance, finance, networks, scale-up and impact) of these businesses to understand how they drive the value propositions and their impact on the wider transition. This is followed by a discussion on a broader business and policy perspective of the Sufficiency-based Circular Economy.